Ginsenoside Rb1 Promotes Hepatic Glycogen Synthesis to Ameliorate T2DM Through 15-PGDH/PGE2/EP4 Signaling Pathway - Liang M; Zhan W; Wang L; Bei W; Wang W (Diabetes, Metabolic Syndrome and Obesity, 2023)
Mingjie Liang,1,2,* Wenjing Zhan,1,2,* Lexun Wang,1,2 Weijian Bei,1,2 Weixuan Wang1,2 1Traditional Chinese Medicine Research Institute, Guangdong Pharmaceutical University, Guangzhou, Guangdong Province, People’s Republic of China; 2Guangdong Provincial Research Center of Integration of Traditional Chinese Medicine and Western Medicine in Metabolic Diseases, Guangdong Pharmaceutical University, Guangzhou, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weixuan Wang, Guangdong Pharmaceutical University, No. 280, Waihuan East Road, University Town, Guangzhou, Guangdong Province, 510006, People’s Republic of China, Tel +86-020-39352607, Email wangweixuan@gdpu.edu.cnPurpose: Ginsenoside Rb1 (Rb1), one of the crucial bioactive constituents in Panax ginseng C. A. Mey., possesses anti-type 2 diabetes mellitus (T2DM) property. Nevertheless, the precise mechanism, particularly the impact of Rb1 on hepatic glycogen production, a crucial process in the advancement of T2DM, remains poorly understood. 15-hydroxyprostaglandin dehydrogenase (15-PGDH) is responsible for prostaglandin E2 (PGE2) inactivation. A recent study has reported that inhibition of 15-PGDH promoted hepatic glycogen synthesis and improved T2DM. Therefore, herein, we aimed to investigate whether Rb1 ameliorated T2DM through 15-PGDH/PGE2-regulated hepatic glycogen synthesis.Methods: By combining streptozotocin with a high-fat diet, we successfully established a mouse model for T2DM. Afterward, these mice were administered Rb1 or metformin for 8 weeks. An insulin-resistant cell model was established by incubating LO2 cells with palmitic acid. Liver glycogen and PGE2 levels, the expression levels of 15-PGDH, serine/threonine kinase AKT (AKT), and glycogen synthase kinase 3 beta (GSK3β) were measured. Molecular docking was used to predict the binding affinity between 15-PGDH and Rb1.Results: Rb1 administration increased the phosphorylation levels of AKT and GSK3β to enhance glycogen synthesis in the liver of T2DM mice. Molecular docking indicated that Rb1 had a high affinity for 15-PGDH. Moreover, Rb1 treatment resulted in the suppression of elevated 15-PGDH levels and the elevation of decreased PGE2 levels in the liver of T2DM mice. Furthermore, in vitro experiments showed that Rb1 administration might enhance glycogen production by modulating the 15-PGDH/PGE2/PGE2 receptor EP4 pathway.Conclusion: Our findings indicate that Rb1 may enhance liver glycogen production through a 15-PGDH-dependent pathway to ameliorate T2DM, thereby offering a new explanation for the positive impact of Rb1 on T2DM and supporting its potential as an effective therapeutic approach for T2DM.Keywords: ginsenoside Rb1, type 2 diabetes mellitus, 15-hydroxyprostaglandin dehydrogenase, prostaglandin E2, hepatic glycogen synthesis